Spatial relationships of the human chorionic gonadotropin (hCG) subunits in the assembly of the hCG-receptor complex in the luteinized rat ovary. - Hwang, J (1984)
In an attempt to examine the spatial relationships of the human chorionic gonadotropin (hCG) subunits in the assembly of the hCG-receptor complex, the recombined 125I-labeled hCG, with label in either the alpha subunit or the beta subunit, was cross-linked to the luteinizing hormone (LH)/hCG receptor. The efficacy of the cross-linking of the 125I-alpha subunit or the 125I-beta subunit of hCG to the LH/hCG receptor was then examined. The autoradiographic profile of 125I-hCG-receptor complex containing the label in the alpha subunit of hCG showed that the alpha subunit can cross-link with all four subunits of the LH/hCG receptor. However, only one faint labeled band, corresponding to Mr = 68,000, was detected when the 125I-hCG-receptor complex with label in the beta subunit was subjected to sodium dodecyl sulfate/polyacrylamide gel electrophoresis under reducing conditions. When the electrophoresis was performed under nonreducing conditions, the Mr 68,000 band disappeared concomitantly with the accumulation of radioactivity in the high molecular weight region. These results indicated that the beta subunit of hCG, unlike the alpha subunit, can cross-link only weakly with the smallest subunit of the LH/hCG receptor. A comparison of the differential effectiveness of the cross-linking of 125I-alpha subunit with 125I-beta subunit of hCG to the LH/hCG receptor suggests that both alpha and beta subunits of hCG are intimately associated with the receptor, but the bulk of the beta subunit of hCG is buried in between the receptor and the alpha subunit of hCG. On the basis of our data, a model for the spatial arrangement of hCG subunits in the hCG-receptor complex is proposed.